Tinjauan Literatur: Gambaran Pengetahuan Remaja terhadap Risiko Pernikahan Dini - Elena Savira; Izra Maghfira Hadi; Trifonia Ardath; Yenny Trisnawati; Wahyudi (PT. Saha Kreasi Indonesia, 2025)
Early marriage is a marriage performed by individuals who have not reached the legal minimum age. This phenomenon remains a social and public health problem in Indonesia due to its various negative impacts, particularly for women, such as the risk of pregnancy complications, anemia, psychological disorders, and educational and economic barriers. Midwifery students, as future health workers, play a crucial role in educating the public about the dangers of early marriage. However, the effectiveness of this role is greatly influenced by their level of knowledge. This review aims to determine the level of knowledge among adolescents regarding the risks of early marriage. The method used in this study was a literature review. Journal searches were conducted on the Google Scholar article portal, PubMed, and databases. The inclusion criteria were journals published between 2020 and 2025, using the keywords